ANALISIS KRITIS M. QURAISH SHIHAB TERHADAP PENGULANGAN KISAH NABI MUSA DALAM AL-QUR’AN - Romziana, Luthviyah; Rahmaniyah, Nur Wahyuni (JURNAL ISLAM NUSANTARA, 2021)
This study aims to analyze the repetition of the story of the Prophet Musa according to Quraish Shihab in the book of al-Misbah interpretation and what goals and lessons can be applied to Millennials like today. The type of research used is a qualitative approach, with library research techniques in data collection. Based on the results of the study, it was found that; First, the purpose of the story of Prophet Musa being repeated in the Koran according to Quraish Shihab is to strengthen and strengthen the heart of the Prophet Muhammad. Second, the wisdom from the story of the Prophet Moses, something hated can lead to good. Second, Allah gave a sign or guidance as Prophet Moses was given the sign of a blazing fire. Third, Allah is Willing and chooses whoever is worthy according to Him as choosing Prophet Moses as ulul azmi and fostering a sense of courage, patience, and perseverance as well as the persistence of Prophet Moses against the arrogance of the king of Pharaoh and his people.